Hydraulic conductance of dentin after treatment with fluoride toothpaste containing sodium trimetaphosphate microparticles or nanoparticles - Favretto, Carla Oliveira [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Toledo, Priscila Toninatto Alves [UNESP]; Pedrini, Denise [UNESP] (Springer Nature, 2020)
Objectives: To evaluate the hydraulic conductance of dentin after treatment with fluoride toothpastes containing sodium trimetaphosphate microparticles (TMPmicro) or nanoparticles (TMPnano). Materials and methods: The dentinal tubules of bovine dentin blocks (4 × 4 × 1 mm) were unobstructed for determination of the maximum hydraulic conductance of the dentin. The dentin blocks were randomized into four groups (n = 15/group) of toothpastes (placebo, 1100 ppm F, and 1100 with 3% TMPmicro or 3% TMPnano) which were applied for 7 days (2×/day) using a brushing machine. The dentin surface (5/group) was analyzed by scanning electron microscopy. The hydraulic conductance post-treatment was measured in the other ten blocks. Thereafter, the same blocks were immersed in citric acid (pH 3.2) for 1 min, and the conductance was determined again. The data were submitted to 2-way ANOVA repeated measures, followed by the Student-Newman-Keuls test (p < 0.05). Results: The percentage conductance reduction post-treatment for the groups were placebo = 1100 ppm F < 1100 TMPnano < 1100 TMPmicro (p < 0.001). After acid attack, the percentage reduction was placebo < 1100 ppm F < 1100 TMPnano < 1100 TMPmicro (p < 0.001). The toothpastes containing TMP showed the highest obliteration of dentinal tubules. Conclusions: The addition of TMPmicro to fluoride toothpaste produced a greater reduction in hydraulic conductance when compared with 1100 ppm F toothpaste. Clinical relevance: The increased capacity of toothpastes containing TMP to reduce hydraulic conductance indicates their potential to reduce symptoms of dentinal hypersensitivity.
Keywords: Dentifrices; Dentin; Dentin permeability; Fluorides; Phosphates